Replication of Mitochondrial DNA. Circular Replicative Intermediates in Mouse L Cells - Robberson, Donald L. (1972)
The frequency, composition, and structure of circular replicating forms of mitochondrial DNA, including two new forms described here, suggest a scheme for the mode of replication of this DNA.